Synthesis and Structural Studies of trans-[Bromo-Bis(Dimethylglyoximato] Cobalt(III) Complexes Containing Heterocyclic Nitrogen Donor Ligands - Nayak, S.C.; Das, P.K.; Sahoo, K.K. (Asian Journal of Chemistry, 2010)
Cobalt(III) complexes of the type [Co(DH)2LBr] where DH = dimethylglyoximato, anion L = (pyridine, piperidine, quinoline, isoquinoline, triazole, indole, benzimidazole, benzotriazole, carbazole) have been isolated and characterized on the basis of physicochemical methods. The chemical analyses are in complete agreement with the above formula of the compounds. The IR spectra reveal the hydrogen bonding and bonding from nitrogen of the ligand to the cobalt. The NMR spectra indicate the stereochemistry of the compound. The UV spectra indicate the octahedral geometry of the complexes.